Analysis of Factors Influencing the Acceptance of the Indodax Application Using the UTAUT 2 Model - Raffi Abdillah Putra Alisia; Anita Wulansari; Rafika Rahmawati (Universitas Islam Kuantan Singingi, 2025)
This study investigates the key factors influencing user acceptance of the Indodax application, a leading cryptocurrency trading platform in Indonesia, by employing the UTAUT 2 (Unified Theory of Acceptance and Use of Technology 2) framework. The model focuses on four core variables—Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions—to assess their impact on users’ Behavioral Intention to adopt the platform. Data were collected from 417 respondents using an online questionnaire, and the relationships among variables were analyzed using SmartPLS 4.0 with the bootstrapping technique. The hypothesis testing results confirmed that all proposed hypotheses were supported, indicating that each of the identified factors significantly contributes to users' intentions to use the application. Among the variables, Performance Expectancy and Facilitating Conditions were found to have the strongest impact on users' Behavioral Intention. Nevertheless, Effort Expectancy and Social Influence also demonstrated significant positive effects. These outcomes emphasize the importance of improving user experience by enhancing system usability, leveraging social influence, and strengthening supporting infrastructure. Overall, the study offers valuable insights for developers, platform providers, and policymakers in developing strategies to encourage broader adoption of cryptocurrency platforms like Indodax and to support the growth of the digital asset ecosystem in Indonesia.